Determinants of adherence to antiretroviral drugs among people living with HIV/AIDS in the Ife-Ijesa zone of Osun state, Nigeria - Muhammed O. Afolabi; Kayode T. Ijadunola; Adesegun O. Fatusi; Olayinka A. Olasode (AOSIS, 2009)
Background: The advent of antiretroviral (ARV) drugs has transformed HIV/AIDS into a chronic manageable disease and strict adherence is required for the medication to be effective. However, factors influencing adherence to ARV therapy (ART) vary from country to country. Method: 120 subjects who received ARV drugs at a federal government-designated ART site located within the Obafemi Awolowo University Teaching Hospital complex, (OAUTHC), Ile-Ife, and a community-based non-governmental organisation, Living Hope Care (LIHOC), Ilesa, from February to May 2006 were serially recruited and studied. Relevant data were collected using an interviewer-administered, patient medication adherence questionnaire. Focus group discussions were also held among the subjects to further elicit qualitative information on factors influencing adherence to ART. Results: The age of participants ranged from 21 to 65 years with a mean age of 40.2 + 10.3 years. Participants had been on ARV drugs for a period ranging between three and 60 months. The overall adherence rate in the study population was 44%. 66% of participants who accessed ARV drugs from LIHOC, Ilesa, had good adherence while only 14% of participants who accessed ARV drugs from OAUTHC, Ile-Ife, had good adherence. Participants with good adherence did not pay funds for the preliminary ARV eligibility investigations and they were also offered regular adherence counselling. These facilities were barely available in the group with poor adherence. Demographic factors such as age, gender and marital status did not seem to have any significant association with adherence level (p > 0.05). Conclusion: The level of adherence was high in a cohort of PLWHA accessing ARV drugs in Ilesa while it was low among PLWHA receiving ART in Ife. The most important reasons for this difference were lack of funds for investigations and poor psycho-social counselling.